To what ends and by what means? the social justice implications of contemporary school finance theory and policy - edited by Gloria M. Rodriguez (New York Routledge, 2007)
This unique collection examines the social justice implications of contemporary economic, finance, and budgeting policies affecting the K-12 education system in the United States. The authors included in this volume provide critiques and explorations of several established theories and policy approaches that undergird contemporary thinking in the field of school finance. These explorations offer themselves as foundations for building new frameworks to understand how school finance policies might better support broader changes needed to improve the educational conditions faced by those individuals and groups traditionally underrepresented in economic, political, and social policy arenas
Includes bibliographical references and index.
Keywords: Education--Social aspects--United States